Effect of friction massage and post facilitation stretch in relieving symptoms related to upper cross syndrome: A randomized clinical trial - Zahoor Ahmed; Ataur Rahman Shahi; Khaista Bacha; Mahnoor Ali (The Rehabilitation Journal)
Background: Upper Cross Syndrome (UCS) is a postural dysfunction that often results from prolonged poor posture, associated with neck pain, shoulder discomfort, reduced range of motion, and muscle fatigue, and significantly impacts daily activities and quality of life. Friction massage (FM) and post-facilitation stretch (PFS) are gaining attention for their potential effectiveness in relieving symptoms and improving muscular balance.